Perilaku Konsumtif dalam Perspektif Gender - Adibah Yahya; Inna Nisawati Mardiani; Agus Fuadi; Ridwan Muhsoni (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research is motivated by the consequences of the global influence of information and technological developments that have an impact on the behavior of the younger generation. One form of this behavior is consumptive behavior. This behavior attacks the younger generation, especially students. One of the conveniences obtained in technological developments is e-money (electronic money). The use of e-money which is quite easy can form consumptive behavior. In addition to the convenience provided by e-money, the existence of e-commerce also tends to shape consumptive behavior. The existence of discount offers and ease of payment stimulates individuals to consume through e-commerce. Individuals who have a financial attitude can reflect a good level of financial management, so that a high financial attitude will reduce consumptive behavior. This study aims to determine the effect of e-money, e-commerce, and financial literacy on consumptive behavior in a gender perspective. The population of this study were students of the Faculty of Economics and Business, Pelita Bangsa University. The research method uses quantitative descriptive analysis, with research sources based on the results of the questionnaire. Data testing uses validity, reliability, classic assumption tests, and hypothesis testing. The test results state that women's gender consumptive behavior is not influenced by money, e-commerce, and financial literacy. For male gender, consumptive behavior is influenced by the use of e-commerce and the level of financial literacy, while e-money has no effect on consumptive behavior. The results show that in general the level of use of e-commerce greatly influences consumptive behavior among students of the Faculty of Economics and Business, Pelita Bangsa University.